PENGARUH PENGGUNAAN VIDEO CONFERENCE DALAM MATA PELAJARAN PAI TERHADAP MOTIVASI BELAJAR SISWA KELAS VIII DI SMP NEGERI - Elinda Sari; Arief Ardiansyah; Mutiara Sari Dewi (VICRATINA, 2022)
The spread of the Covid-19 outbreak which has an impact on various fields, especially the education sector. To avoid the spread and process of direct interaction, all activities are carried out online or remotely. Educators make every effort so that the teaching and learning process is effective with the existing facilities. This study aims to determine the use of video conferencing in SMP Negeri 1 Turen, to determine student learning motivation and to determine the effect of using video conferencing in the form of a zoom application on student learning motivation. This study uses an experimental method with analysis of the Independent sample T-test as a hypothesis test. Based on the research results obtained with a significance value below 0.05, this study proves that the use of video conferencing in the form of a zoom application has an influence on student learning motivation.